KOMEDI SATIRE PADA PODCAST “MUSUH MASYARAKAT”: (Studi Deskriptif Kualitatif Resepsi Generasi Z terhadap komedi satire Pada Podcast Musuh Masyarakat episode 109 : “Pejabat Tidak Perlu Ramah”) - Illah, Atok; Febrianita, Roziana; Arviani, Heidy (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
Musuh Masyarakat podcast is a comedy podcast accessible through application called NOICE. The type of comedy featured in featured in this podcast is satire comedy. Satire comedy is a form of humor that includes sarcasm directed toward a subject by representing its flaws or mistakes. Satire comedy is a means of conveying social criticism that is considered to minimize the occurrence of offense. Satire comedy in this podcast is intended to provide constructive criticism and facilitate beneficial discussion. However, satirical comedy employs figurative expression and contains irony that can be interpreted freely by the audience. This can lead to misunderstandings that may result in offense. The purpose of this study is to determine how Generation Z accept satire comedy on the episode 109 of Musuh Masyarakat podcast "Pejabat Tidak Perlu Ramah". The method used is descriptive qualitative. Data collection techniques used are in-depth interviews and documentation. This research uses Stuart Hall's Encoding-Decoding reception analysis model. The results show that the reception among informants varied, but there were no informants who completely rejected that satire comedy is a means of conveying social criticism that can minimize offense, provide constructive criticism, and provide a space for beneficial discussion. Factors of life experience, culture and religious beliefs influence the variety of meanings and acceptance of informants.